Analysis of Inpatient Satisfaction at the Aceh Singkil Regional General Hospital - -, Adinda (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2024)
In 2018, the patient satisfaction rate in Indonesia was 42.8%, still below the standard set by the Indonesian Ministry of Health of 95%. Improved healthcare services are necessary to ensure patient satisfaction. Good service quality arises from patient perceptions, who expect the service to meet their expectations. This study aims to analyze inpatient satisfaction at the Aceh Singkil Regional General Hospital. The research method used was quantitative with a cross-sectional approach. The population consisted of 320 patients or their families, with a sample size of 175 people drawn using accidental sampling using a questionnaire. The study was conducted in July 2024. Data were analyzed using univariate, bivariate (chi-square), and multivariate (logistic regression) analyses. 83 (47.7%) respondents were dissatisfied, 128 (73.1%) reported good doctor service, 132 (75.4%) reported good nurse service, and 98 (56.0%) reported good administrative service. There was a correlation between doctor service (p-value 0.014), nurse service (p-value 0.012), and administrative service (p-value 0.000) and patient satisfaction. The most dominant variable influencing patient satisfaction was administrative service (p-value 0.000) with an OR of 8.105. It is hoped that hospitals can improve patient satisfaction by providing friendly and attentive service and training for healthcare staff.